Clinical and functional outcome of total knee arthroplasty in osteoarthritic patients at a tertiary care center in Kerala: a prospective study - P. K., Navaneeth; S., Prakash Nayar; Jose, T. M. (International Journal of Advances in Medicine, 2022)
Background: Osteoarthritis affects the knee joint more frequently than any other joint. Osteoarthritis is a chronic joint disease that affects the older age group, women more frequently, and is associated in 90% of cases with a varus deformity of the knee. The following study was conducted to evaluate the functional outcome of total knee arthroplasty in osteoarthritis using the knee society score. Methods: The study was conducted in patients treated for osteoarthritis of the knee joint at Jubilee Mission Medical College and Research Institute, Thrissur, Kerala during the period from December 2019 to March 2022. Thirty patients diagnosed with osteoarthritis of the knee joint were taken into the study, all were undergone total knee arthroplasty. Patients were followed up at 4 weeks, 12 weeks, and 24 weeks. Results: The sample consisted of thirty osteoarthritic patients with 8 males and 22 were females. The patients’ ages ranged from 45-75 years. Among these 30 patients, 14 involved the right side, and 16 involved the left knee joint. The mean pre-operative knee clinical score was 36.93 which was improved to post-operative 84.70 following total knee arthroplasty. The mean pre-operative knee functional score was 16.83 which was improved to post-operative 71.17 following total knee arthroplasty. The outcome was rated as per knee society score. We got excellent results in 25 cases (83%), good in 3 (10%), and fair in 2 patients (7%) according to knee clinical score whereas 8 excellent (27%), 16 good (53%), 5 fair (17%) and 1 poor (3%) results were found according to knee functional score. Conclusions: Total knee arthroplasty shows drastic improvement in the functional ability of the patient and the ability of the patient to get back to a pre-disease state, which is mainly because of pain-free joint movements, reflected by the improvement in the post-operative knee clinical score and knee functional score.